Why Intermediality — if at all? - Gumbrecht, Hans (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2003)
As much as the concept of intertextuality has known a great success within social sciences because it represented the closure of a conception of the world understood as readable, in the same way, intermediality will have a true reach only if it permits us to liberate ourselves from this model and open a new array of problematics. Through this rapid reconstruction of conceptual paradigms, what is at stake is the possibility of rethinking medias outside of the procedures of hermeneutics and the sole universe of significance.